A prática jurídica entre a “bainha” e a “faca”: para (re)pensar o direito a partir da perspectiva de quilombolas nos conflitos entre a Vale e os territórios de Santa Rosa dos Pretos e Monge Belo, em Itapecuru-Mirim/MA - Bruzaca, Ruan Didier (2020)
The following thesis aims to analyze the judicial practice which arise in the lawsuits evolving Vale S/A and the quilombolas’ territories of Santa Rosa dos Pretos and Monge Belo which are located in the municipality of Itapecuru-Mirim/MA/BRA, with the purpose of identifying their living practices especially when it comes to the Law. This thesis has the objective of understanding the bigger picture in which these great economical endeavors contrast with the traditional people and communities, such as indigenous people, babaçu coconut breakers, river communities, rural communities, and, through it, comprehend, in these lawsuits, how their lifestyles are inserted in the environment. In the first chapter, I present the legislation (“the sheath”) that contemplates the rights of the quilombolas after the enacting of the 1988 Brazilian constitution, while identifying that the same legislation and legal discourse make it possible that other subjects of rights exist. In the second chapter, I expose the judicial practice and arguments that aim to maintain the continuity of the activities of Vale S/A, and how that influences in closing the possibilities previously mentioned in the first chapter. In the third chapter, I bring the quilombola organization (“the knife”), observing their perspective about judicial practice and how that is also part of their lives. The research object of the present thesis is precisely the judicial practice in the lawsuit that involve those regions, which are the cases of Santa Rosa dos Pretos and Monge Belo vs Vale S/A, Quilombolas and indigenous people vs Vale and finally Vale vs Santa Rosa dos Pretos and Monge Belo. The research query is to ask, taking into account the context of those lawsuit conflicts, in what measure the judicial practice of the interpretative community includes the way of living of the quilombolas when it comes to solving those conflicts involving the great economical endeavors and what is the perspective of the quilombolas in regards to the Law. I produced a circular research in conceptual, methodological and empirical steps, according to U. Flick. Prior to the research, I undertook a documental research which consisted of gathering the lawsuits which include Vale S/A in the state of Maranhão. After the contact with the field camp in Itapecuru-Mirim, I selected the examplary cases, proceeding to the analysis of the content of the lawsuit and the identification of the agents of the institutions of the justice system so that semi-structured interviews could be taken. The research also has an anthropological nature, given that, beyond conducting interviews with the leaders of the quilombola regions, I also produced an ethnography, using as research material the notes and pictures taken in the field. The theoretical framework used in this thesis is based on the amerindian perspectivism of E. V. de Castro, along with antidogmatism and philosophy of language of L. Wittgenstein, which made possible the identification of the perspective of the quilombolas in regards to the Law, as seen as pratice through the jus realism and antiformalism of E. Santoro. I conclude with the thesis that only the “sheath” is insufficient for quilombola struggles, since it only serves because of the “knife”, having its substance filled by the resistances, struggles, festivities and cultures existing in quilombola territories. With the correlation between the “knife” and the “sheath” - between the struggle and the predicted rights - there is a counterpoint to the violation of the rights of black rural communities involving capital and the State, insofar as the insertion of the lived, the struggle of those communities, contribute to a juridical language marked by openings and to a legal practice that does not relegate the quilombolas’ importance to the Law.